FRI0581-HPR The effect of muscular strength on scapular kinematics in asymptomatic shoulders with or without scapular dyskinesis. (23rd January 2014) - Camci, E.; Duzgun, I.; Hayran, M.; Baltaci, G.; Karaduman, A.
Abstract : Background: Scapular dyskinesis is alternations in scapular position and motion, has been associated with various shoulder pathologies [1 ]. An appropriate scapular upward rotation is considered to be essential for normal shoulder function and serratus anterior and trapezius muscles works together as a force couple to dynamically control this movement [2 ]. However, the effect of muscular strength of force couple on scapular kinematics hasn't been studied. Objectives: To investigate the muscular strength of force couple muscles on scapular upward rotation during shoulder abduction in asymptomatic shoulders with or without scapular dyskinesis. Methods: Sixty-four asymptomatic shoulders without were included to the study. Observational clinical assessment has used to categorize the presence of scapular dyskinesis using yes/no method [3 ]. Maximal isometric strength of serratus anterior, upper trapezius and lower trapezius muscles was evaluated with handle-hand dynamometer to assess muscular strength [4 ]. Three-dimensional scapular orientation was recorded by electromagnetic system during shoulder elevation in frontal plane according to ISB recommendations to assess amount of scapular upward rotation [5 ]. Student t-test and Pearson's correlation were used for statistical comparisons. Results: The results of observational assessment showed that 62.5% (n=40) of asymptomatic shoulders were with scapular dyskinesis and 37.5% (n=24) were normal. Comparison the muscle strength and scapular upward rotation between shoulders with or without scapular dyskinesis showed no statistical difference (p>0.05). Also, there were no correlation between muscular strength and scapular upward rotation through humerothoracic elevation in both study groups (p>0.05). Conclusions: Scapular dyskinesis may be observed in asymptomatic shoulders and surprisingly, shoulders with scapular dyskinesis have not any kinematic differences when comparing to the shoulders without scapular dyskinesis. It may be possible to have kinematic alternation in presence of pain and further studies needed in this area. Another important finding of this study showed that muscular strength of force couple seems not affect the related scapular rotation in asymptomatic shoulders. Neuromuscular properties such as activation levels and recruitment patterns of the scapular muscles would have critical role on normal scapular movement patterns. References: Kibler, W.B. and J. McMullen, Scapular dyskinesis and its relation to shoulder pain. J Am Acad Orthop Surg, 2003. 11 (2): p. 142-51. Bagg, S.D. and W.J. Forrest, Electromyographic study of the scapular rotators during arm abduction in the scapular plane. Am J Phys Med, 1986. 65 (3): p. 111-24. Uhl, T.L., et al., Evaluation of clinical assessment methods for scapular dyskinesis. Arthroscopy, 2009. 25 (11): p. 1240-8. Michener, L.A., et al., Scapular muscle tests in subjects with shoulder pain and functional loss: reliability and construct validity. Phys Ther, 2005. 85 (11): p. 1128-38. Wu, G., et al., ISB recommendation on definitions of joint coordinate systems of various joints for the reporting of human joint motion--Part II: shoulder, elbow, wrist and hand. J Biomech, 2005. 38 (5): p. 981-992. Disclosure of Interest: None Declared